The noradrenergic agent reboxetine plus the antimuscarinic hyoscine butylbromide reduces sleep apnoea severity: a double‐blind, placebo‐controlled, randomised crossover trial. (14th July 2021) - Lim, Richard; Messineo, Ludovico; Grunstein, Ronald R.; Carberry, Jayne C.; Eckert, Danny J.
Abstract : Key points: Recent animal and human physiology studies indicate that noradrenergic and muscarinic processes are key mechanisms that mediate pharyngeal muscle control during sleep. The noradrenergic agent reboxetine combined with the anti‐muscarinic hyoscine butylbromide has recently been shown to improve upper airway function during sleep in healthy individuals. However, whether these findings translate to the clinically relevant patient population of people with obstructive sleep apnoea (OSA), and the effects of the agents on OSA severity, are unknown. We found that reboxetine plus hyoscine butylbromide reduced OSA severity, including overnight hypoxaemia, via increases in pharyngeal muscle responsiveness, improvements in respiratory control and airway collapsibility without changing the respiratory arousal threshold. These findings provide mechanistic insight into the role of noradrenergic and anti‐muscarinic agents on upper airway stability and breathing during sleep and are important for pharmacotherapy development for OSA. Abstract: The noradrenergic agent reboxetine combined with the anti‐muscarinic hyoscine butylbromide has recently been shown to improve upper airway function during sleep in healthy individuals. However, the effects of this drug combination on obstructive sleep apnoea (OSA) severity are unknown. Accordingly, this study aimed to determine if reboxetine plus hyoscine butylbromide reduces OSA severity. Secondary aims were to investigate the effects on key upper airway physiology and endotypic traits. Twelve people with OSA aged 52 ± 13 years, BMI = 30 ± 5 kg/m 2, completed a double‐blind, randomised, placebo‐controlled, crossover trial (ACTRN12617001326381). Two in‐laboratory sleep studies with nasal mask, pneumotachograph, epiglottic pressure sensor and bipolar fine‐wire electrodes into genioglossus and tensor palatini muscles were performed separated by approximately 1 week. Each participant received either reboxetine (4 mg) plus hyoscine butylbromide (20 mg), or placebo immediately prior to sleep. Polysomnography, upper airway physiology and endotypic estimates of OSA were compared between conditions. Reboxetine plus hyoscine butylbromide reduced the apnoea/hypopnoea index by (mean ± SD) 17 ± 17 events/h from 51 ± 30 to 33 ± 22 events/h ( P  = 0.005) and nadir oxygen saturation increased by 6 ± 5% from 82 ± 5 to 88 ± 2% ( P  = 0.002). The drug combination increased tonic genioglossus muscle responsiveness during non‐REM sleep (median [25th, 75th centiles]: −0.007 [−0.0004, −0.07] vs . −0.12 [−0.02, −0.40] %maxEMG/cmH2 O, P  = 0.02), lowered loop gain (0.43 ± 0.06 vs . 0.39 ± 0.07, P  = 0.01), and improved airway collapsibility (90 [69, 95] vs . 93 [88, 96] %eupnoea, P  = 0.02), without changing the arousal threshold ( P  = 0.39). These findings highlight the important role that noradrenergic and muscarinic processes have on upper airway function during sleep and the potential for pharmacotherapy to target these mechanisms to treat OSA. Key points: Recent animal and human physiology studies indicate that noradrenergic and muscarinic processes are key mechanisms that mediate pharyngeal muscle control during sleep. The noradrenergic agent reboxetine combined with the anti‐muscarinic hyoscine butylbromide has recently been shown to improve upper airway function during sleep in healthy individuals. However, whether these findings translate to the clinically relevant patient population of people with obstructive sleep apnoea (OSA), and the effects of the agents on OSA severity, are unknown. We found that reboxetine plus hyoscine butylbromide reduced OSA severity, including overnight hypoxaemia, via increases in pharyngeal muscle responsiveness, improvements in respiratory control and airway collapsibility without changing the respiratory arousal threshold. These findings provide mechanistic insight into the role of noradrenergic and anti‐muscarinic agents on upper airway stability and breathing during sleep and are important for pharmacotherapy development for OSA.